Controllability analysis and optimal control of biomass drying with reduced order models. (May 2020) - Berner, Marc Oliver; Scherer, Viktor; Mönnigmann, Martin
Highlights: Process models for the drying of biomass are derived by applying model reduction methods to distributed parameter system Controllability properties of the industrial process are analyzed by combining reduced models and empirical Gramians Optimal control problems are solved with reduced models to find energy-optimal drying procedures Abstract: Complex industrial processes such as the drying of combustible biomass can be modeled with partial differential equations. Due to their complexity, it is not straightforward to use these models for the analysis of system properties or for solving optimal control problems. We show reduced order models can be derived and used for these purposes for industrial drying processes.